1985
DOI: 10.1111/j.1346-8138.1985.tb01554.x
|View full text |Cite
|
Sign up to set email alerts
|

Humoral Immunity in Patients With Tinea Versicolor

Abstract: Thirty patients with tinea versicolor (TV) and 30 age/sex-matched healthy individuals were used to evaluate the anti-Pityrosporum orbiculare antibodies (anti-PO) using indirect immunofluorescence. Both serum IgG and IgM type anti-P, orbiculate existed in both patients and controls. The antibody titers were significantly higher in patients, especially in those with erythematous lesions. Further analysis was performed and discussed in 120 controls at various ages. This investigation supports again that P. orbicu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
6
0
1

Year Published

1998
1998
2015
2015

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 26 publications
(22 reference statements)
2
6
0
1
Order By: Relevance
“…This finding suggested that opsonized M. furfur could be recognized via complement receptor type 3, and supported the results reported by Szabo et al in the case of C. albicans [17]. M. furfur could activate the alternative and classical pathways of complement (unpublished data), and it is reported that natural antibody against M. furfur existed in normal human serum [18, 19]. But in this paper, we did not demonstrate the recognition of M. furfur via Fc receptor in the experiment using heat‐inactivated serum, because heating at 56°C would lead to denaturation of complement components, not of antibody.…”
Section: Discussionsupporting
confidence: 89%
“…This finding suggested that opsonized M. furfur could be recognized via complement receptor type 3, and supported the results reported by Szabo et al in the case of C. albicans [17]. M. furfur could activate the alternative and classical pathways of complement (unpublished data), and it is reported that natural antibody against M. furfur existed in normal human serum [18, 19]. But in this paper, we did not demonstrate the recognition of M. furfur via Fc receptor in the experiment using heat‐inactivated serum, because heating at 56°C would lead to denaturation of complement components, not of antibody.…”
Section: Discussionsupporting
confidence: 89%
“…Antibodies against Malassezia are found in both pityriasis versicolor patients and normal subjects 46 . In some experiments, antibody titres have been shown to be elevated in patients, 50–52 although other investigators have found no difference between patients and controls 53 . It appears that a significant humoral immune response occurs only with infection by the fungus, rather than in mere colonization.…”
Section: Immune Response To Malassezia In Pityriasis Versicolormentioning
confidence: 99%
“…The first study to examine the levels of different isotypes of immunoglobulins was reported by Wu and Chen (476). They found that the mean total IgG and total IgM levels in patients were reportedly significantly higher than the levels in controls (P Ͻ 0.005), but the method of statistical analysis was not stated.…”
Section: Pityriasis Versicolormentioning
confidence: 99%